2019
DOI: 10.26442/00403660.2019.12.000086
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial factors and coronary heart disease

Abstract: Article is devoted to a research of interrelation of psychosocial factors and courses of coronary heart disease (CHD). The anxiety, a depression, social isolation of patients with CHD is considered. Need of identification of psychosocial factors at patients with CHD for the purpose of their correction and improvement of the forecast of sick CHD and quality of their life is shown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Despite the occurrence of brilliant advances in the field of prevention and treatment, coronary heart disease (CHD) is still known as the most common cause of death throughout the world. Altho ugh it is not possible to precisely recognize the patients at risk of developing coronary artery disease (CAD), influences of certain risk factors, genetic and environmental, have been quite understood (1,2). The most familiar risk factors include aging, hypertension, diabetes mellitus (DM), smoking, lack of physical activity, mental stress, obesity, and being overweight.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the occurrence of brilliant advances in the field of prevention and treatment, coronary heart disease (CHD) is still known as the most common cause of death throughout the world. Altho ugh it is not possible to precisely recognize the patients at risk of developing coronary artery disease (CAD), influences of certain risk factors, genetic and environmental, have been quite understood (1,2). The most familiar risk factors include aging, hypertension, diabetes mellitus (DM), smoking, lack of physical activity, mental stress, obesity, and being overweight.…”
Section: Introductionmentioning
confidence: 99%
“…Previous researches have shown that the incidence rate of CHD is different from men to women, and the prognosis of female is worse than that of male [5,6]. In addition, there are many factors associated with CHD, such as psychological stress, work-related stress, lifestyle and so on [7][8][9][10]. CHD is usually prevented and treated by normalization of blood lipid pro le, hypertension control, nutritional supplements in clinic [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%